2014
DOI: 10.1111/ppl.12296
|View full text |Cite
|
Sign up to set email alerts
|

Iron allocation in leaves of Fe‐deficient cucumber plants fed with natural Fe complexes

Abstract: Iron (Fe) sources available for plants in the rhizospheric solution are mainly a mixture of complexes between Fe and organic ligands, including phytosiderophores (PS) and water-extractable humic substances (WEHS). In comparison with the other Fe sources, Fe-WEHS are more efficiently used by plants, and experimental evidences show that Fe translocation contributes to this better response. On the other hand, very little is known on the mechanisms involved in Fe allocation in leaves. In this work, physiological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…HS can be obtained from different sources (Halpern et al, 2015), however it is worth to note that interesting results on root proliferation and nutrient uptake have been obtained using low concentrations of water-soluble molecules isolated from peat Schmidt et al, 2007). Particularly, supplying plants with Fe complexed to water extractable humic substances led to a higher translocation of iron to the leaves, as compared to other Fe complexes (Tomasi et al , 2009Zanin et al, 2015); this effect might be relevant when considering alternatives to synthetic Fe-chelate as well as for biofortification programmes.…”
Section: Biostimulants and Humic Substancesmentioning
confidence: 96%
See 2 more Smart Citations
“…HS can be obtained from different sources (Halpern et al, 2015), however it is worth to note that interesting results on root proliferation and nutrient uptake have been obtained using low concentrations of water-soluble molecules isolated from peat Schmidt et al, 2007). Particularly, supplying plants with Fe complexed to water extractable humic substances led to a higher translocation of iron to the leaves, as compared to other Fe complexes (Tomasi et al , 2009Zanin et al, 2015); this effect might be relevant when considering alternatives to synthetic Fe-chelate as well as for biofortification programmes.…”
Section: Biostimulants and Humic Substancesmentioning
confidence: 96%
“…Most of the leaf vegetable products are actually minimally processed, packed in air or in modified atmosphere, refrigerated and consumed within 5e10 days from harvest (Rolle & Chism, 1987). Ready-to-use leaf vegetables are thus particularly requested by consumers for their quality, convenience, but also for the increased awareness about the relations between health status and consumption of fresh vegetable rich in phytochemicals with protecting capability (Zanin et al, 2009;Zanin et al, 2011). Based on these expectations, the sensory and nutritional qualities of fresh-cut vegetables are extremely important (Kader, 2008).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although there is a high availability of this element in the applied nutrient solution, the plants did not accumulate higher concentrations. This was probably because cucumber plants optimize the use of Fe when the source is chelated [36,37].…”
Section: Micronutrient Accumulationmentioning
confidence: 99%
“…It has been clearly demonstrated that Fe complexed by low molecular weight water‐extractable humic fractions can be utilized by cucumber plants with an efficiency higher than that observed for other Fe sources, such as Fe‐ethylenediaminetetraacetic acid (EDTA), Fe‐Cl 3 , and Fe‐citrate ( Pinton et al, ). This effect was not only ascribed to the specific plant Fe acquisition mechanism at the root level ( Tomasi et al, ), but also to the mechanisms involved in the allocation of the nutrient at the leaf level ( Tomasi et al, , ; Zanin et al, ).…”
Section: Introductionmentioning
confidence: 99%